Microcontroller implementation of a Harmonic Control Arrays system - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
Harmonic Control Arrays (HCA) is a technique that is based on adjusting the harmonic components of the control signal for systems with periodic references and disturbances. In this study, a microcontroller implementation of the HCA method, the algorithm, and the results has been represented. A first order system, consisting of a resistor and a capacitor has chosen as the plant, and a periodic reference signal have been applied on it. © 2017 IEEE.